Caspase‐6/Gasdermin C‐Mediated Tumor Cell Pyroptosis Promotes Colorectal Cancer Progression Through CXCL2‐Dependent Recruitment of Myeloid‐Derived Suppressor Cells - Hanchao Gao; Yikun Yao; Weilong Li; Zigan Xu; Wenjun Hu; Kewang Luo; Peishan Chen; Wanjing Shang; Shaodong Luan; Guojun Shi; Mengtao Cao; Pengfei Chen (Advanced Science)
Abstract Gasdermin (GSDM) family proteins mediate inflammatory cell pyroptosis and exert critical contributions to the pathogenesis of gastrointestinal cancers, infections, and gut mucosal inflammation. Gasdermin C (GSDMC) is overexpressed in human colorectal cancer (CRC); however, the molecular mechanisms underlying GSDMC regulation of CRC tumorigenesis are largely elusive. Here, it is found that both GSDMC expression and activation are significantly elevated in human and mouse CRC tissues. Gsdmc2/3/4 deficiency attenuates tumor progression in both chemically induced CRC mouse model and spontaneous intestinal tumor model. Mechanistically, under hypoxia and low‐glucose condition, GSDMC2/3/4 are directly activated by Caspase‐6, but not by Caspase‐8, as previously reported in other cancers. GSDMC2/3/4‐mediated pyroptosis in tumor cells leads to the release of high mobility group protein B1 (HMGB1), which enhances the expression of chemokine attractant C‐X‐C motif chemokine 2 (CXCL2) in surrounding tumor cells. Subsequently, the elevated CXCL2 secretion from tumor cells promotes the recruitment of myeloid‐derived suppressor cells (MDSCs) into the tumor microenvironment (TME) through C‐X‐C chemokine receptor type 2 (CXCR2), thereby facilitating CRC progression. These findings reveal a mechanism by which Caspase‐6/GSDMC‐mediated tumor cell pyroptosis, in response to hypoxic and low‐glucose conditions, remodels the immunosuppressive microenvironment through CXCL2‐dependent recruitment of MDSCs. These results identify GSDMC as a potential drug target for CRC therapy.